PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT DALAM MENCEGAH PENULARAN COVID-19 - Nisa, Sara Holiviya; Nugroho, Setiyo Adi (Jurnal Keperawatan Profesional, 2022)
The Covid-19 infection spreads very quickly throughout the world so it is necessary to prevent the spread of Covid-19 by implementing Clean and Healthy Living (PHBS) behaviors such as washing hands using soap or hand sanitizer, wearing masks when doing activities outside the home and applying coughing and sneezing etiquette. Through PHBS, it is hoped that the community can maintain, maintain and improve their health. The purpose of this literature study is to find out the effectiveness of implementing Clean and Healthy Lifestyles both in the community and health service agencies in preventing the transmission of Covid-19. Database searches include Google Scholar, Google Scholar, Garuda Portal, and Science Direct with the keywords PHBS, COVID-19, Clean and healthy lifestyle. The criteria for selected articles are 2017-2021, with full text and in English and Indonesian. This literature study used 16 articles that met the inclusion criteria. The application of Clean and Healthy Living Behavior (PHBS) can be applied to increase awareness of individual health in an effort to prevent the transmission of Covid-19.